STUDY OF HAZARDOUS WASTE TREATMENT AND MANAGEMENT FOR THE OIL AND GAS INDUSTRIES - M. Mulyono; R. Desrina; Evita H. Legowo (Scientific Contributions Oil and Gas, 2002)
Study of hazardous waste treatment and management for the oil and gas industries has been conducted by Lemigas Team to observe the existing guidelines and the implementation of the guidelines in hazardous waste management. The study also includes a selection of the government regulation that should be considered in the hazardous waste treatment and management for the oil and gas industries. Results of the study indicate that the oil industry does not conduct treatment processes for all hazardous wastes that are generated. Some of them, especially those of non-specific hazardous wastes are stored in a temporary storage facility and managed off site for treatment or disposal to a commercial hazardous waste facility. The off-site waste management requires the use of a document termed a manifest for tracking its transport on a "cradle-to-grave" basis. The most prominent problem faced by the oil production industries, however, is the vast generation of wastes from production operation activities such as drilling mud, oil contaminated soil, and oil tank sludge and pit sludge. All of these wastes need to be handled properly. This paper presents the results of the study describing the existing guidelines used by the oil and gas industry and its implementation as well as reviewing the government regulation related to hazardous waste management and the technologies that can be applied in mitigating the hazardous wastes generated by the oil and gas industries.